Preparation and characterization of self-assembled short-chain glucan aggregates (SCGAs) derived from various starches. (May 2021) - Oh, Seon-Min; Park, Cheon-Seok; Kim, Young-Rok; Baik, Moo-Yeol
Abstract: Short chain glucan aggregates (SCGAs) forming ability of starches from different botanical sources and physicochemical characteristics of the produced SCGAs from various starches were investigated. SCGAs were obtained by enzymatic hydrolysis and centrifugation followed by self-assembly of their hydrolysates in supernatant. Size of SCGAs was 0.68–1.30 μm and its shape was spherical with high agglomeration. Yield showed negative correlation with amylose content (R 2  = 0.9024) indicating that starches with low amylose content or high amylopectin content produced more SCGAs. Chain length distribution of SCGAs prepared from various starches were similar possibly due to the removal of large and insoluble portions using centrifugation after enzymatic hydrolysis. Main constituent of SCGAs was a B1 chain (13 = DP ≤ 24). All SCGAs showed B-type crystal pattern with relative crystallinity of 14.5–19.4%. DSC endothermic transition of SCGAs occurred at higher temperature than native starch indicating the improved thermal stability. Colloidal dispersion stability of SCGAs was increased with increasing absolute value of zeta potential and decreasing particle size. Consequently, SCGAs can be obtained from all kinds of starches regardless of amylose content and type of crystallinity, and have distinctive physicochemical properties. This study provides helpful information on the preparation of SCGA from various starches and their characteristics resulting that SCGAs can be customized with appropriate properties using different starches. Graphical abstract: Image 1 Highlights: Main constituent of all SCGAs was a B1 chains (13 ≤ DP ≤ 24). The XRD and DSC results of SCGAs were not consistent. Dispersion stability of SCGAs were dependent on particle size and zeta potential. SCGAs can be customized with appropriate properties using different starches.